(untitled) (LACCEI, 2024)
The purpose of this research is to carry out a geophysical study through the application and use of electrical tomography, which is capable of supplying and processing fundamental information in the characterization of the subsoil of the former Shudal Dump, Cajamarca, 20220 as well as determine the level of infiltration generated by leached fluids in dumps. That is why, the use of geophysical methods is shown to be dependent on the interpretation and research work, since within this study the integration and use of the largest possible amount of data obtained is given, where the variation of the abrupt conductivity and resistivity of the subsoil will be reflected in the sources of contamination by leached fluids, due to the fact that the physical properties of the fill materials during their activity present different geological formations. The main axis of the research is geophysical prospecting as a fundamental tool to find the distribution in subsoil resistivity factor. In this way, data was collected in the area longitudinally and transversally, with the data obtained the construction of the resistivity profiles was carried out and three areas with different resistivity’s were identified, the first ranges from 10-80 Ohm, the second from 80-320 Ohm and the third from 320-4100 ohm. Each grouping of resistivity’s by zone was cataloged as a different lithology interpreting them as clayey sands, sandstones and quartzite’s respectively..